Answer:
y = 2x + 3 → Gradient / slope = 2 → Y - intercept = 3
y = -3x + 3 → Gradient / slope = -3 → Y - intercept = 3
Explanation:
y = mx + c
This is the standard way an equation of a line is written. The 'm' of the line is the slope/gradient and the 'c' is the y - intercept. You can find the x-intercept by making y = 0. When the questions asks you to find the gradient you should never put 'x' after it only the number so
y = 2x + 3
Gradient / slope = 2
Y - intercept = 3
y = -3x + 3
Gradient / slope = -3
Y - intercept = 3